2012
DOI: 10.1038/nm.2850
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic excitation after febrile seizures induces ectopic granule cells and adult epilepsy

Abstract: Temporal lobe epilepsy (TLE) is accompanied by an abnormal location of granule cells in the dentate gyrus. Using a rat model of complex febrile seizures, which are thought to be a precipitating insult of TLE later in life, we report that aberrant migration of neonatal-generated granule cells results in granule cell ectopia that persists into adulthood. Febrile seizures induced an upregulation of GABA(A) receptors (GABA(A)-Rs) in neonatally generated granule cells, and hyperactivation of excitatory GABA(A)-Rs c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(155 citation statements)
references
References 58 publications
6
148
1
Order By: Relevance
“…As bumetanide is rapidly eliminated in rodents and only poorly penetrates into the brain [60], we are currently trying to overcome these disadvantages by either administering more lipophilic prodrugs of bumetanide or inhibiting its metabolism in rodents, or both. Interestingly, the lack of any significant effects of single drug treatment with bumetanide in our study [60] may be due to the model (pilocarpine) used because in a more recent study by Koyama et al [62] bumetanide was shown to prevent the development of epilepsy after febrile seizures in rats. Thus, again, the type and severity of epileptogenic brain insult is important when studying the antiepileptogenic efficacy of compounds.…”
Section: Examples For Synergistic Drug Combinationsmentioning
confidence: 63%
See 1 more Smart Citation
“…As bumetanide is rapidly eliminated in rodents and only poorly penetrates into the brain [60], we are currently trying to overcome these disadvantages by either administering more lipophilic prodrugs of bumetanide or inhibiting its metabolism in rodents, or both. Interestingly, the lack of any significant effects of single drug treatment with bumetanide in our study [60] may be due to the model (pilocarpine) used because in a more recent study by Koyama et al [62] bumetanide was shown to prevent the development of epilepsy after febrile seizures in rats. Thus, again, the type and severity of epileptogenic brain insult is important when studying the antiepileptogenic efficacy of compounds.…”
Section: Examples For Synergistic Drug Combinationsmentioning
confidence: 63%
“…Other potential targets include NKCC1 [57,62] and modulators of neuroinflammation, that is, IL-1, COX-2, and transforming growth factor β [63]. Further interesting findings (not discussed in detail here) include 1) administration of decoy oliognucleotides limiting the transcriptional repressor, neuron-restrictive silencer factor (NRSF), which is initiated after SE, resulted in a 70 % reduction in the number of SRS during the ensuing 2 weeks [65]; 2) pharmacological depletion of a microRNA, miR-134, initiated after SE reduced the occurrence of SRS when tested weeks later [66]; and 3) treatment with atipamezole, an α2-adrenergic receptor antagonist, starting 1 week after SE, reduced frequency and severity of SRS tested after wash-out from atipamezole, indicating a disease-modifying effect [67].…”
Section: Discussionmentioning
confidence: 99%
“…GABAergically-induced ectopic granule cells in the dentate gyrus during development in FS rats [29] ); and (2) a decrease in HCN (hyperpolarization-activated cyclic nucleotide-gated) channels, which are associated with hippocampal rhythms [31,32] , induced by FSs during epileptogenesis [30] . Here we found that the CA3 pyramidal neuronal cell body circumference occupied by inhibitory presynaptic terminals was significantly increased in FS rats at P35.…”
Section: Discussionmentioning
confidence: 99%
“…Bumetanide has also shown promise in preventing epileptogenesis in other animal models with postnatal human correlates, including febrile seizures leading to subsequent temporal lobe epilepsy (8). While this may be a more readily translatable use of bumetanide, establishing this approach as a treatment for epileptogenesis poses other challenges.…”
Section: Nurture Trumps Nature In a Model Of Heritable Epilepsy: Willmentioning
confidence: 99%